Mengungkap Aspek Sedekah dalam Transaksi Mangpaindan Doi pada Masyarakat Lunjen Enrekang - Andi Suwandi Putra Suaib; Wahyuddin Abdullah; Muslimin Kara (Jurnal Iqtisaduna, 2018)
The focus of this research is the practice of transaction and doi and aspects of charity in the transaction. This study uses a qualitative paradigm with a phenomenal approach. The data validity testing uses data triangulation techniques and theory triangulation to improve data validity and reliability. The results of this study are (1) the mechanism of transactions that are carried out and carried out by individual Lunjen people has no witnesses, no written form, and no return agreement. (2) Money inflation in other transactions and transactions occurs between the lending time and payment of the debt. (3) The results of the qardh alms calculation obtained state that each muqridl gives alms qardh and also muqtaridl obtains the opposite. Transactions and doi have sharia added value (shari'ah value added) such as economic value added to the charity aspect of value reduction (inflation), mental added value to altruistic feelings and spiritual added value, namely sincerity and a sense of God's presence